No effect of user fee exemption on perceived quality of delivery care in Burkina Faso: a case-control study - Philibert, Aline (BioMed Central, 2014)
BACKGROUND: Although many developing countries have developed user fee exemption policies to move towards universal health coverage as a priority, very few studies have attempted to measure the quality of care. The present paper aims at assessing whether women’s satisfaction with delivery care is maintained with a total fee exemption in Burkina Faso. METHODS: A quasi-experimental design with both intervention and control groups was carried out. Six health centres were selected in rural health districts with limited resources. In the intervention group, delivery care is free of charge at health centres while in the control district women have to pay 900 West African CFA francs (U$2). A total of 870 women who delivered at the health centre were interviewed at home after their visit over a 60-day range. A series of principal component analyses (PCA) were carried out to identify the dimension of patients’ satisfaction. RESULTS: Women’s satisfaction loaded satisfactorily on a three-dimension principal component analysis (PCA): 1-provider-patient interaction; 2-nursing care services; 3-environment. Women in both the intervention and control groups were satisfied or very satisfied in 90% of cases (in 31 of 34 items). For each dimension, average satisfaction was similar between the two groups, even after controlling for socio-demographic factors (p = 0.436, p = 0.506, p = 0.310, respectively). The effects of total fee exemption on satisfaction were similar for any women without reinforcing inequalities between very poor and wealthy women (p ≥ 0.05). Although the wealthiest women were more dissatisfied with the delivery environment (p = 0.017), the poorest were more highly satisfied with nursing care services (p = 0.009). CONCLUSION: Contrary to our expectations, total fee exemption at the point of service did not seem to have a negative impact on quality of care, and women’s perceptions remained very positive. This paper shows that the policy of completely abolishing user fees with organized implementation is certainly a way for developing countries to engage in universal coverage while maintaining the quality of care.